Hubungan antara hs-CRP, Adiponektin, Fetuin A terhadap Resistensi Insulin pada Pria Dewasa Muda dengan Obesitas Sentral - Amudi, Tulus; Pandelaki, Karel; Palar, Stella (e-CliniC, 2021)
Abstract: Obesity has quite a lot of risk factors for the incidence of metabolic diseases such as insulin resistance, diabetes mellitus, dyslipidemia, and metabolic syndrome. The accumulation of adipocytes causes the formation of chronic inflammatory mediators, and disrupts adipokine derived from adipocytes. These inflammatory mediators cause hepatocytes to secrete several types of proteins such as C-reactive protein and fetuin A into the blood circulation that are thought to cause insulin resistance in obesity cases. This study was aimed to determine the relationship among levels of hs-CRP, adiponectin, and fetuin A, and insulin resistance in adult male subjects with central obesity. This was an observational study with a cross sectional design. Subjects were young adult males with central obesity at Prof. Dr. R. D. Kandou Hospital, Manado. The results showed that 30 subjects had a mean hs-CRP level of 0.18 mg/dL (±0.16) which was higher than normal value. There was a positive and significant correlation between hs-CRP and HOMA-IR (r=0.380, p<0.023). There was a negative and insignificant correlation between adiponectin and Homa IR (r =-0.278, p=0.136), and there was no significant correlation between fetuin A and HOMA IR (r -0.048, p=0.801). In conclusion, among young adult males with central obesity there was an increase in hs-CRP level above normal value and there was a significant relationship between increased hs-CRP and insulin resistanceKeywords: fetuin-A, high sensitive C-reactive protein, adiponectin, HOMA-IR, central obesity Abstrak: Obesitas memiliki faktor risiko yang cukup banyak terhadap kejadian penyakit metabolik seperti resistensi insulin, diabetes melitus, dislipidemia, dan sindrom metabolik. Akumulasi adiposit menyebabkan terbentuknya mediator inflamasi kronik sehingga sintesis adipokin oleh adiposit terganggu. Mediator inflamasi tersebut juga menyebabkan hepatosit menyekresi beberapa jenis protein seperti C-reaktif protein dan fetuin A ke dalam sirkulasi darah yang diduga meyebabkan resistensi insulin pada kasus obesitas. Penelitian ini bertujuan untuk mengetahui hubungan antara kadar hs-CRP, adiponektin, dan fetuin A dengan resistensi insulin pada subjek pria dewasa dengan obesitas sentral. Jenis penelitian ialah observasional dengan desain potong lintang. Subyek penelitian ialah pria dewasa muda dengan obesitas sentral di RSUP Prof. Dr. R. D. Kandou Manado. Hasil penelitian mendapatkan 30 subyek dengan rerata kadar hs-CRP 0,18 mg/dl (±0,16) lebih tinggi dari nilai normal. Terdapat hubungan korelasi positif dan bermakna antara hs-CRP dan HOMA-IR (r=0,380, p<0,023); hubungan korelasi negatif dan tidak bermakna antara adiponektin dan Homa IR (r=-0,278, p=0,136); tidak didapatkan hubungan bermakna antara Fetuin A dengan HOMA IR (r=-0.048 dan p=0,801). Simpulan penelitian ini ialah pada pria dewasa muda dengan obesitas sentral terdapat peningkatan kadar hs-CRP melebihi nilai normal dan terdapat hubungan bermakna antara peningkatan hs-CRP dengan resistensi insulin.Kata kunci: fetuin-A, high sensitive C-reactive protein, adiponectin, HOMA-IR, obesitas sentral